Early Idiomatic Knowledge Acquisition: A Cornerstone for Language Proficiency (London Journal of Research In Humanities and Social Sciences, 2025)
Idioms are essential language skills that enhance language proficiency in all languages. Idiomatic knowledge help individuals to be proficient in communication in both verbal and written language. However, they are not explicitly incorporated in the early years of schooling and this could be the reason there are persisting literacy challenges in South Africa. The literacy reports show that Foundation Phase learners’ language skills are not well developed. They reveal that learners have challenges in both reading and writing. The purpose of this paper is to advocate for explicit integration of idioms in Grade 3 curriculum with an aim to increase the learner’s language proficiency in their home languages. This paper is grounded in Social constructivism theory to reveal how idioms as scaffolding tools support language proficiency. It is guided by qualitative research, interpretive paradigm and case study research design. Data was collected through semi-structured interviews. Participants were two Grade 3 teachers and a thematic analysis helped in analyzing interview data. The findings showed that the integration of idioms could improve the learners’ creative writing skills, they can help them to write meaningful sentences and paragraphs.
Keywords: curriculum development; Constructivism; Philippine Education; student-centered; Lacking animal protection in Georgia; animal ethics as a moral deficit in the 21st century; cultural indifference in the Transcaucasus; lack of awareness; Social Isolation; Connected Generation; Digital Communication; Online Communities; Social Media Impact; Psychological Well-being; Digital Age Loneliness; Virtual Relationships; Technology and Human Interaction; Creative writing; idioms; language proficiency; sounding native like; vocabulary